Design and Analysis of Two-Link Discrete Flexible Manipulator. Issue 1 (February 2021) - Punniyawarthana, S; Mohanraj, T
Abstract: Proposed two-link flexible manipulators suit the requirement of larger work volume than the traditional flexible manipulators and handle high payloads equal to that of rigid manipulators. The simulation was performed on the Computer-Aided Design (CAD) model of the Motoman HC-10DT, a Human-Collaborative robot. During the analysis, one link of the manipulator was modified as a flexible manipulator for which static and modal analysis was done and compared the results with the actual link of the robot to validate the proposed design. The kinematic analysis was also done to find the reach of the modified robot. Total deformation on both the flexible manipulator and the actual link of the robot was 0.2mm but the maximum von Mises stress acting on the flexible manipulator was 2.97% lesser than that of the rigid link of the robot. Eventually, the safety factor of the flexible manipulator was higher compared to the rigid link. The factor of safety of the upper link is 1.41 and the lower link is 1.51 whereas the actual link of the robot has the safety factor of 1.30.